Prvi Slovar makedonskega knjižnega jezika s stališča kodifkacije makedonskega jezika - Nikolovski, Gjoko (Slavia Centralis, 2020)
THE FIRST MACEDONIAN LANGUAGE DICTIONARY FROM THE STANDPOINT OF THE CODIFICATION OF THE MACEDONIAN LANGUAGE This paper deals with the frst Macedonian language dictionary with Serbo-Croatian translations, specifcally concerning its role in the consolidation and further development of the Macedonian language.